2016
DOI: 10.3844/ajavsp.2016.91.99
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Probiotics on Coccidia, <i>H</i>. Contortus and Markers of Infection in Goats

Abstract: Immunostimulants can induce nonspecific resistance against parasites. The use of probiotics to control development of animal gastrointestinal parasites could help reduce the risks of infestation. In this study, we investigated the effects of probiotics administration on gastrointestinal parasites coccidia, H. contortus and markers of infection. A cocktail of probiotics mix including Bifidobacterium longum, Bifidobacterium breve, Lactobacillus acidophilus, Lactobacillus reuteri and Lactobacillus rhamnosus (8.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…The results from this study corroborated with the findings from earlier workers. A similar result was reported in which probiotics had no effect on body weight (Jinturkar et al, 2009, Gyenai et al, 2016, Whitely et al, 2009). In addition, previous studies conducted by Kumar et al (2016) showed that supplementing probiotics to barbari goats had no effect on body weight.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The results from this study corroborated with the findings from earlier workers. A similar result was reported in which probiotics had no effect on body weight (Jinturkar et al, 2009, Gyenai et al, 2016, Whitely et al, 2009). In addition, previous studies conducted by Kumar et al (2016) showed that supplementing probiotics to barbari goats had no effect on body weight.…”
Section: Discussionsupporting
confidence: 73%
“…Fecal egg count is a parameter widely used to determine parasitic infection in animals (Kaplan et al, 2004). Previous study conducted by Gyenai et al, (2016) reported that probiotic mix had an effect on increase of egg per gram but in our studies treatment had no effect on fecal egg count. Treatment had no effect on FAMACHA scores and PCV.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…These sites include the oral cavity, intestines, vagina and the skin [34]. In ruminants, probiotics are usually administered orally [35][36][37][38][39][40][41][42][43]. A study by Deng et al [44,45] utilized intravaginal infusion as mode of administering probiotics (containing a lactic acid bacteria mixture) to periparturient cows.…”
Section: Administration Of Probioticsmentioning
confidence: 99%